Improving the social emotional abilities of special needs children through block play - Fajriah, Dina; Ajat; Amaliani, Rita; Gustini, Eti; Salmiani (Pusat Studi Gender dan Anak, 2024)
The ability of young children to interact with others, control their own emotions, and recognize and react to the feelings of others are all considered social-emotional abilities in early life. Special needs children do not have the opportunity to play with appropriate play materials. Consequently, children with special needs frequently must fully explore their social-emotional development. Since play is a crucial component of children's growth and development, it is anticipated that using block play methods will enhance students' social-emotional skills and prevent boredom in the classroom. Children's social-emotional abilities, like focus and concentration, self-assurance, and cooperation, can be improved through block games. This study aims to describe how learning through block media is implemented, how difficulties arise, and how learning through block media is implemented to enhance children's social-emotional capacities. The classroom action research design was applied in this study. Data was gathered at TKIT A'amillah through interviews, paperwork, and filed notes from five kids. The study's findings indicate that one of the best approaches for enhancing the knowledge and abilities of kids with special needs is through the block technique; the usage of blocks supports the proper development of children's social-emotional skills.